Discharge β-blocker Use and Race after Coronary Artery Bypass Grafting - Wesley T. O'Neal; Jimmy Thomas Efird; Stephen Wayne Davies; Jason Benjamin O'Neal; William F. Griffin; T. Bruce Ferguson; W. Randolph Chitwood; Alan eKypson (Frontiers Media S.A., 2014)
Introduction: The use of discharge β-blockers after cardiac surgery is associated with a long-term mortality benefit. β-blockers have been suggested to be less effective in black cardiovascular patients compared with whites. To date, racial differences in the long-term survival of coronary artery bypass grafting (CABG) patients who receive β-blockers at discharge have not been examined.Methods: A retrospective cohort study was conducted of patients undergoing CABG between 2002 and 2011. Long-term survival was compared in patients who and who were not discharged with β-blockers. Hazard ratios (HR) and 95% confidence intervals (CI) were computed using a Cox regression model. P-for-interaction between race and discharge β-blocker use was computed using a likelihood ratio test.Results: A total of 853 (88%) black (n=970) and 3,038 (88%) white (n=3,460) patients had a history of β-blocker use at discharge (N=4,430). Black patients who received β-blockers survived longer than those not receiving β-blockers and the survival advantage was comparable with white patients (black: adjusted HR=0.33, 95%CI=0.23-0.46; white: adjusted HR=0.48, 95%CI=0.39-0.58; p-for-interaction=0.74). Among patients discharged on β-blockers, we did not observe a long-term survival advantage for white compared with black patients (HR=1.2, 95%CI=0.95-1.5). Conclusions: β-blocker use at discharge was associated with a survival advantage among black patients after CABG and a similar association was observed in white patients.